UPAYA PENCEGAHAN PATOLOGI BIROKRASI - Netti, Herza; Aisyah, Aisyah; Hidayati, Sri; Roza, Silvia; Oktaviani, Elget (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In a modern government administration system, bureaucracy is crucial for running the government and serving the public. However, internal problems often lead to poor performance and undermine public trust. The reality experienced within government bureaucracies, such as convoluted work procedures, uneven workloads, slowness, inefficiency, rigidity, a lack of transparency, and corrupt behavior, is described as a sick bureaucracy or bureaucratic pathology. This study aims to determine the conditions and various practices of bureaucratic pathology in Indonesia and their prevention in order to create an efficient bureaucracy. The method used in this study is a qualitative approach with literature review techniques. The results show that the history of bureaucracy in Indonesia is closely related to national culture and is influenced by existing cultural issues. Culture and habits are difficult to change because they are closely related to morality, which is the initial symptom of bureaucratic pathology.